2001
DOI: 10.1007/pl00011360
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy in Ophthalmology: From Experimental Tool to Applications In Vivo

Abstract: Raman spectroscopy is a qualitative and quantitative optical technique for determining the molecular composition of matter. Improvements in spectroscopic instruments, especially the modality to detect low light level signals extended the Raman technique to biomedical applications, even in delicate structures like the eye. The purpose of this paper was to make an inventory of performed applications of Raman spectroscopy in biomedical science and especially in ophthalmology. A literature search was done using Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 154 publications
0
35
0
Order By: Relevance
“…The occurrence of small spectral features in the anterior chamber of the eye which are native to this medium were to be expected since different biological molecules with various Raman activity already exist in this medium [11,13]. In order to be able to distinguish the specific peaks of the antibiotic ceftazidime and antifungal amphotericin B, we had to search for those peaks specific to these drugs that would not coincide with the inherent peaks of the aqueous humor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of small spectral features in the anterior chamber of the eye which are native to this medium were to be expected since different biological molecules with various Raman activity already exist in this medium [11,13]. In order to be able to distinguish the specific peaks of the antibiotic ceftazidime and antifungal amphotericin B, we had to search for those peaks specific to these drugs that would not coincide with the inherent peaks of the aqueous humor.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy has been successfully utilized in rabbit eyes for different types of investigations [11,20] and it may offer an effective tool to non-invasively assess the concentration of various intravitreal drugs as tested in both the aqueous humor and vitreous humor. Bauer et al have already shown the feasibility of Raman spectroscopy in detecting the drug Trusopt in the tear film of the eye in a pharmacokinetic study [21] and we have demonstrated its potential in monitoring the antiviral drug Ganciclovir in a previous study [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports utilizing Raman spectroscopy for ophthalmological investigation focused on detection of human macular pigment and glutamate in the eyes, in which the excitation laser wavelength was selected to resonate with the vibrational modes of the pigment/glutamate molecules, and an enhanced Raman signal was achieved. 25,27 To acquire a Raman signal directly from the RGC cells without the resonance enhancement effects, the autofluorescence background has to be removed before the analysis of the vibrational bands takes place. The most common methods for background removal, as the one currently used in this study, are based on digital signal subtraction utilizing the common feature of fluorescent backgrounds-a smooth function of the emission wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrational spectroscopies, Raman and infrared, have been extensively used in biology and medicine as analytic and diagnostic tools from their early beginnings [5], [6], [7] and [8]. Rapid computerisation and the discovery of laser accelerated the number of these studies reported in books and conference proceedings [9], [10] and [11].…”
Section: Introductionmentioning
confidence: 99%